Catalases of the polyextremophylic andean isolate Acinetobacter sp. Ver 3 confer adaptive response to H2O2 and UV radiation - (:unkn) unknown (Wiley, 2020)
The polyextremophilic strain Acinetobacter sp. Ver3 isolated from high-altitude Andean lakes exhibits elevated tolerance to UV-B radiation and to pro-oxidants, a feature that has been correlated to its unusually high catalase activity. The Ver3 genome sequence analysis revealed the presence of two genes coding for monofunctional catalases: AV3KatE1 and AV3KatE2, the latter harboring an N-terminal signal peptide. We show herein that AV3KatE1 displays one of the highest catalytic activities reported so far and is constitutively expressed at relatively high amounts in the cytosol, acting as the main protecting catalase against H2O2 and UV-B radiation. The second catalase, AV3KatE2, is a periplasmic enzyme strongly induced by both peroxide and UV, conferring supplementary protection against pro-oxidants. The N-terminal signal present in AV3KatE2 was required not only for transport to the periplasm via the twin-arginine translocation pathway, but also for proper folding and subsequent catalytic activity. The analysis of catalase distribution among 114 Acinetobacter complete genomes revealed a great variability in the catalase classes, with A. baumannii clinical isolates exhibiting higher numbers of isoenzymes and the most variable profiles.
Keywords: Acinetobacter; Andean wetlands; Catalase; Oxidative stress; UV radiation